Geoinformatics in applied geomorphology - Anbazhagan, Siddan; Subramanian, S. K.; Yang, Xiaojun, 1965- (Boca Raton, FL : CRC Press, 2011)
'With recent innovations in the arena of remote sensing and geographic information systems, the use of geoinformatics in applied geomorphology is receiving more attention than ever. Geoinformatics in Applied Geomorphology examines how modern concepts, technologies, and methods in geoinformatics can be used to solve a wide variety of applied geomorphologic problems, such as characterization of arid, coastal, fluvial, aeolian, glacial, karst, and tectonic landforms; natural hazard zoning and mitigations; petroleum exploration; and groundwater exploration and management.' -- Publisher's website.
Includes bibliographical references and index.
Keywords: Geomorphology; Geomorphology -- Geographic information systems; Geographic information systems; Geospatial data